Analysis of Treatment Results in Primary Germ Cell Tumours with Mediastinal Location: Own Experience - Kowalski, Dariusz; Knetki-Wróblewska, Magdalena; Winiarczyk, Kinga; Jaśkiewicz, Piotr; Orłowski, Tadeusz; Langfort, Renata; Krzakowski, Maciej; Olszewski, Michał (Advances in respiratory medicine, 2014)
Introduction: Primary germ cell tumours with mediastinal location comprise 1–6% of mediastinal tumours and 2–5% of all germ cell tumours occurring in adults. They are identified mostly in the 3rd decade of life, in 90% of cases in men. The most common symptoms are dyspnea, chest pain, cough, fever and weight loss. The aim of the present study was the analysis of our own results of treatment of primary germ cell tumours with mediastinal location, and a review of the literature concerning this subject. Material and Methods: Five patients (4 males, 1 female) median age 27.8 years (range 23–30 years) treated in the period from 1999 to 2009 in Maria Sklodowska-Curie Memorial Cancer Centre and Institute of Oncology, Department of Lung Cancer and Chest Tumours in Warsaw, due to germinal tumours with primary mediastinal location, entered the study. Results: All patients received chemotherapy according to the BEP regimen. All patients achieved an objective response to treatment. Two patients died due to disease progression in spite of II- and III-line treatment. Three patients are still in follow-up. The median survival time was 55.8 months (range 8.0–120.0 months). Conclusions: Primary mediastinal germ cell tumours have worse prognosis than do those with gonadal location. Based on our observations and review of the literature, it can be concluded that the results of treatment of non-seminoma type germ cell tumours with primary mediastinal location remain poor. Patients who develop early recurrence or progression during first-line chemotherapy are particularly at risk of unfavourable outcome. Identification of new standards of treatment in tumours resistant to cisplatin require further studies evaluating the effectiveness of new generation cytostatic drugs.